Plasticity of photosynthetic heat tolerance in plants adapted to thermally contrasting biomes. (29th January 2018) - Zhu, Lingling; Bloomfield, Keith J.; Hocart, Charles H.; Egerton, John J.G.; O'Sullivan, Odhran S.; Penillard, Aurore; Weerasinghe, Lasantha K.; Atkin, Owen K.
Abstract: In many biomes, plants are subject to heatwaves, potentially causing irreversible damage to the photosynthetic apparatus. Field surveys have documented global, temperature‐dependent patterns in photosynthetic heat tolerance ( P HT ); however, it remains unclear if these patterns reflect acclimation in P HT or inherent differences among species adapted to contrasting habitats. To address these unknowns, we quantified seasonal variations in T crit (high temperature where minimal chlorophyll‐ a fluorescence rises rapidly, reflecting disruption to photosystem II) in 62 species native to 6 sites from 5 thermally contrasting biomes across Australia. T crit and leaf fatty acid (FA) composition (important for membrane stability) were quantified in three temperature‐controlled glasshouses in 20 of those species. T crit was greatest at hot field sites and acclimated seasonally (summer > winter, increasing on average 0.34 °C per °C increase in growth temperature). The glasshouse study showed that T crit was inherently higher in species from warmer habitats (increasing 0.16 °C per °C increase in origin annual mean maximum temperature) and acclimated to increasing growth temperature (0.24 °C °C −1 ). Variations in T crit were positively correlated with the relative abundance of saturated FAs, with FAs accounting for 40% of T crit variation. These results highlight the importance of both plastic adjustments and inherent differences determining contemporary continent‐wide patterns in P HT . Abstract : Climate records have revealed increasing frequency, intensity, and duration of heatwave events across Australian continent. Such events have important implications for one of the most important metabolic processes in plants—photosynthesis. Our study combined field and glasshouse temperature‐response curves of photosystem II (PSII) functionality to reveal the extent to which photosynthetic heat tolerance: (a) acclimates to sustained changes in growth temperature; and, (b) differs inherently among species adapted to thermally contrasting environments across the Australian continent.